PENGARUH KONSEP DIRI DAN KINERJA MENGAJAR DOSEN TERHADAP PRESTASI BELAJAR MAHASISWA POLITEKNIK LP3I JAKARTA KAMPUS BLOK M - Herry Syafrial (POLITEKNIK LP3I JAKARTA, 2017)
This research was conducted to determine how much influence the self-concept on student learning achievement at Polytechnic LP3I Jakarta, Blok M Campus, determine how much influence teaching lecturer performance on student learning achievement at Polytechnic LP3I Jakarta, Blok M Campus, and determine how much influence self-concept and teaching lecturer performance simultaneously on student learning achievement at Polytechnic LP3I Jakarta, Blok M Campus. This research uses correlation to see how much the influence of two independent variables and the dependent variable. The population research was all active students period of 2014/2015 at Polytechnic LP3I Jakarta Blok M Campus, amount of 346 students and 78 Students as sample of this research. Each respondent got 25 questions by using a Likert scale. Based on the results of data processing showed that the effect of self-concept of student learning achievement at Polytechnic LP3I Jakarta, Blok M Campus is strong, it means that the relations between the two variables are significant for a strong confidence level. Also the influence of teaching lecturer performance on student learning achievement at Polytechnic LP3I Jakarta, Blok M Campus is strong. While the influence self-concept and teaching lecturer performance on student learning achievement at Polytechnic LP3I Jakarta, Blok M Campus is strong. This shows if self-concept and teaching lecturer performance well-applied will increase student learning achievement. Keywords: Self Concept, Teaching Performance, Learning Achievement.